Violências escolares: falas de educadores - Branco, Maria de Fátima Ferrão Castelo (2014)
This research was developed with the aim of reflecting on the experience of educators about school violence. The study included twenty four teachers from three schools, among them, one public and two private (corporate and other religious one) in the Metropolitan Region of Recife. The general objective of this study was: understanding how educators experience school violence in their institutional routine and specific were: to characterize teachers regarding gender, age, length of experience in education, academic education; describe the experiences of educators about school violence and identify how educators perceive themselves in relation to the issue of school violence. From a qualitative methodology as a tool for data collection used collective conversations with script of questions. The results were analyzed based on the theory of Social Representation (RS) with respect to a creative process of cognitive and symbolic elaborations that provide guidance to human behavior, as well as being a mechanism for developing social object by interpersonal communication, group , mass and analysis of collected data we use the Collective Subject Discourse (CSD) because it is a technique of tabulation and organization of qualitative data that is based on the theory of RS. DSC enables, through systematic and standardized procedures, add testimonials without reducing them to numbers. DSC emerged in some central ideas (ICs), described as follows: Dissatisfaction educator / illness; Students' disinterest; Context family / school; Link teacher / student and expressions of violence. The results achieved in this study allows us to assert that the experiences of educators on school violence refer to confrontations caught, every day, for them to establish links between personal and professional well-being in the workplace, in constant search of partnership with families in the process of educating, preserving the affectivity and the ability to deal with the violence that hit the school environment. Keywords: education; school; violence.